An assessment of techniques and practices used to elevate intra‐abdominal pressure when assessing pelvic floor dysfunction. Issue 3 (2nd February 2021) - El‐Hamamsy, Dina; Watson, Alison; Corden, James; Smith, Anthony R. B.; Reid, Fiona M.
Abstract: Aims: To determine terminology and methods for raising intra‐abdominal pressure (IAP) currently used by clinicians to assess pelvic floor dysfunction (PFD) and to measure the effect of these maneuvers on IAP. Methods: Three‐hundred questionnaires were distributed at two scientific meetings in the United Kingdom to determine methods clinicians used to raise IAP and their perceptions of these methods. Twenty healthy volunteers were also recruited to measure the effect of two methods of raising IAP: Valsalva maneuver (VM) and bear down maneuver (BDM). IAP pressure was measured with rectal catheters connected to pressure sensors. The IAP was measured during each maneuver in both standing and supine positions. Results: Maneuvers used in practice were cough (79%), BDM (60%), and VM (38%). 44% of clinicians felt patients found it difficult to raise their IAP. There was uncertainty among clinicians as to which method was the most effective in raising IAP and whether the different methods produced the same rise in IAP. On testing IAP in 20 healthy volunteers, median (interquartile range) IAP generated during BDM; 101 (59.1) cmH2 O was significantly higher than that generated during VM; 80.3 (43.6) cmH2 O ( p < .0001). Conclusion: Clinicians varied widely in the maneuvers they used to raise patients' IAP to test for PFD and there was uncertainty about the maneuvers' effect on IAP. In healthy volunteers, BDM produced significantly higher IAP than VM. We recommend standardization of terminology and techniques used to raise IAP when assessing PFD, to ensure consistency of diagnosis and assessment of treatment outcomes.